Bulk and Mapping Speciation Analyses Unveil the Pattern and Heterogeneity of Cu Species during Organic Waste Treatment - Doelsch, Emmanuel; Le Bars, Maureen; Etschmann, Barbara; Formentini, Thiago; Legros, Samuel; Levard, Clément; Chaurand, Perrine; Basile-Doelsch, Isabelle; Rose, Jérôme; Brunetti, Gianluca; Doolette, Casey; Howard, Daryl L.; et al. (Environmental science & technology, 2024)
Organic wastes (OWs) can be a common source of copper (Cu) contamination of agricultural soils. Here we conducted a comprehensive study of 22 raw and treated OWs sampled at 6 different full-scale OW treatment plants. Bulk XANES analysis findings indicated that the Cu oxidation state was subject to changes throughout the OW treatment process, mostly depending on the anaerobic/aerobic conditions prevailing in each treatment stage. These changes were independent of the OW origin (agricultural, urban or industrial). Cu(I) prevailed in raw OWs and digestates (88–100%), whereas Cu(II) dominated in composts (46–100%). Bulk EXAFS analysis confirmed these observations and revealed that Cu(I) species in raw OWs and digestates consisted mainly of Cu(I)-sulfide (76–100%), while Cu(II) species (60–100%) in composts were Cu(II)-citrate, Cu(II)-carbonate and amorphous Cu(II)-phosphate. Interestingly, we observed that anaerobic digestion was conducive to the formation of crystallized Cu(I)-sulfides at the expense of nanosized and poorly crystalline Cu(I)-sulfide species, and that the recalcitrant Cu(I) species in composts was always crystallized Cu(I)-sulfide. XANES imaging analysis revealed Cu(II) species present in low proportions (2–4%) that were not detected using bulk XAS analysis in raw OWs and digestates. This demonstrated the potential of XANES imaging for probing minor species in complex matrices.